Poster: We Are Well: Eco-Dyeing - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
The poster, ‘We Are Well: Eco Dyeing’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. It showcases the process and product of harvesting. preparing and dyeing with local plants as a means to explore Country. Poster text: Kylie Colemane picked ruby salt-bush from behind her, next to the concrete stairs. The berries just got that burst of colour when you pushed them down. All of this stuff is around us and we just don’t know. We can make art without going to a shop. And it’s all-natural, with no chemicals at all. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Nikki Browne, Melissa Bedford, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.